2011
DOI: 10.4187/respcare.00625
|View full text |Cite
|
Sign up to set email alerts
|

Critical-Thinking Ability in Respiratory Care Students and Its Correlation With Age, Educational Background, and Performance on National Board Examinations

Abstract: BACKGROUND:Critical thinking is an important characteristic to develop in respiratory care students. METHODS: We used the short-form Watson-Glaser Critical Thinking Appraisal instrument to measure critical-thinking ability in 55 senior respiratory care students in a baccalaureate respiratory care program. We calculated the Pearson correlation coefficient to assess the relationships between critical-thinking score, age, and student performance on the clinical-simulation component of the national respiratory car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…95 A group of educators from University of Texas Health Science Center examined the critical thinking ability of a group of respiratory care students in a baccalaureate program. 96 Results of the study indicated that critical thinking did not increase with age. Furthermore, while there was no correlation between critical-thinking score and performance on clinical simulation examinations, there was a significant positive association between strong science-course background and the critical-thinking score.…”
Section: Educationmentioning
confidence: 87%
“…95 A group of educators from University of Texas Health Science Center examined the critical thinking ability of a group of respiratory care students in a baccalaureate program. 96 Results of the study indicated that critical thinking did not increase with age. Furthermore, while there was no correlation between critical-thinking score and performance on clinical simulation examinations, there was a significant positive association between strong science-course background and the critical-thinking score.…”
Section: Educationmentioning
confidence: 87%
“…5 The study was well done and adds to the small body of literature on the factors that promote critical thinking in respiratory care students.…”
mentioning
confidence: 99%
“…Yet much of the literature conducted within the profession of respiratory care has focused on baccalaureate degree programs or higher. Additionally, participants of such studies may have had already studied in the health sciences or have developed a certain level of critical thinking in the duration of their educational career (Wettstein, Wilkins, Gardner, & Restrepo, 2011). Scoring validated by studies may not be applicable as admission criteria for associate degree programs because incoming students have not had exposure to the skill and critical thinking development required to function effectively in the health sciences (Huhn et al, 2011).…”
Section: Problem Statementmentioning
confidence: 99%
“…The students who enter the baccalaureate programs do so with a greater number of prerequisite science courses. According to Wettstein et al (2011), graduates with extensive science coursework have a higher level of critical-thinking ability. In general, the associate degree programs in the area have one to two science courses as program prerequisites and thus might have lower critical-thinking ability within respiratory care.…”
Section: Positionality Statementmentioning
confidence: 99%
See 1 more Smart Citation